Heart's flower the life and poetry of Shinkei - Ramirez-Christensen, Esperanza U. (Stanford Univ. Press, 1994)
His priestly duties and his devotion to Buddhist ideals are directly reflected in the intensely pure, lyrical longing for transcendence that is the most notable quality of his sensibility. Shinkei's life and work also provide a vivid portrayal of a tumultuous period of Japanese history that was one of the defining moments of its culture, when Zen Buddhism began to directly influence the arts